Khanty urban women in the second half of the 20th — early 21st century: continuity of ethnocultural traditions, a view from the “inside” - Voldina T.V. (Вестник археологии, антропологии и этнографии, 2024)
Ethnicity is a dynamic category based on ethnic background. Most clearly it is expressed in the traditional environment, natural for the preservation of cultural traditions, which is associated with ancestral places, rural areas. In recent years, the number of representatives of indigenous peoples of the North living in the cities of Yugra has increased significantly. The main force of national intelligentsia is concentrated in the city of Khanty-Mansiysk, public institutions have been created there that became a part of the modern ethnic culture of the Ob Ugrians. The most representative part of this community are women, they clearly show their creative nature. The purpose of this work is to capture the features of the expression of ethnicity among Khanty women of different generations living in urban conditions, to trace its changes and continuity using the example of resi dents of Khanty-Mansiysk. To assess this topic, a “look from the inside” is characteristic, the author places herself in the center of the study, as she belongs to this community. The stories of famous Khanty women who were born in the 1930s in a traditional environment but became citizens, as well as stories of their daughters and granddaughters born in the city, serve as a “reference”. The author concludes on the natural “blurring” of ethnic identity in city environment. This is a natural process caused by the environment itself, as well as by metisation of urban residents. The process of assimilation of ethnic cultures in urban conditions is faster. The “true” representatives of traditional culture in urban environment are those born in rural areas. The first generation of urban women (“mothers”) keeps in touch with the traditional environment, usually speaks their native language and appears as representatives of ethnic culture. The second generation (“daughters”) takes a marginal position in relation to their native culture and the urbanized environment, they are able to perceive their native culture, but at a different level; they rather carry a universal identity. Representatives of the third generation (“granddaughters”), as a rule, are not speakers of their native language and bearers of the culture, and their ethnic identity is expressed in preserving the memory of their ancestors.